Overview of Potential Application of Pineapple Leaves Fibre (PALF) in Asphalt Mixture Focusing on Rutting Resistance - Hasbullah, Noraain; Abdullah, Mohd Ezree (Recent Trends in Civil Engineering and Built Environment, 2021)
Rutting occurs due to longitudinal depression in wheel path or poor road construction work that can cause many negative impacts to the road pavement. The explore of the potential of Pineapple Leaves Fibre (PALF) as a modifier in asphalt mixture is important. The asphalt mixture modification with natural fibre helps provide good performance, service life and reduce road maintenance costs. Therefore, this study is significant in evaluating PALF potential in asphalt mixture based on the PALF physical, mechanical, and chemical properties. Besides, the Marshall Stability and Indirect Tensile Strength test of asphalt mixture’s performance with PALF from the previous study was also studied. Next, PALF has superior properties as reinforcement in the asphalt mixture to improve the mixture's performance, stabilise the binder during mixing and placement, and minimise pavement distress, especially rutting. Hence, the addition of PALF in asphalt mixture would be beneficial in improving some of the main properties of the pavement and minimise rutting resistance, besides, the Marshall Stability and Indirect Tensile Strength test from the reviewed study show the stronger PALF in asphalt mixture.